Does the mobility of R&D labor increase innovation? - Ulrich Kaiser; Hans Christian Kongsted; Thomas Rønde (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We investigate the effect of mobility of R&D workers on the total patenting activity of their employers. Our study documents how mobile workers affect the patenting activity of the firm they join and the firm they leave. The effect of labor mobility is strongest if workers join from patent-active firms. We also find evidence of a positive feedback effect on the former employer's patenting from workers who have left for another patent-active firm. Summing up the effects of joining and leaving workers, we show that labor mobility increases the total innovative activity of the new and the old employer. Our study which is based on the population of R&D active Danish firms observed between 1999 and 2004 thus provides firm-level support for the notion that labor mobility stimulates overall innovation of a country or region due to knowledge transfer.
urn:nbn:de:bsz:180-madoc-374638
Keywords: J62; C26; 330; labor mobility; innovation; research and development; patenting